GENDER DAN SELF EFFICACY : SEBUAH KAJIAN PERBANDINGAN PADA SISWA SMA NEGERI 1 INDRALAYA - Nuraini, Putri; Mega Putri, Rani (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
This study aims to determine whether there is a comparison of self-efficacy levels between male and female students at SMA Negeri 1 Indralaya. Self-efficacy is an individual's belief in his ability to organize and regulate an action needed to achieve certain goals. The research method used is quantitative with a comparative descriptive approach. The sample in this study amounted to 80 grade XI students, consisting of 36 male students and 44 female students selected using proportionate stratified random sampling technique. The data collection instrument is a Likert scale questionnaire that has been tested for validity and reliability. The results showed that the mean value of self-efficacy of female students (68.22) was slightly higher than male students (66.88), there was no statistically significant difference between the two groups (p = 0.271 > α = 0.05). Thus, gender is not the only factor that can significantly affect the level of self-efficacy of SMA Negeri 1 Indralaya students.